Geoelectric Method Implementation in Measuring Area Groundwater Potential: A Case Study in Barru Regency - Falah, Muh. Darwis (International Journal of Environment, Engineering & Education, 2020)
Geoelectric measurements to detect the presence of groundwater aquifers in the study area by knowing the type of lithology, distribution, thickness, and depth of rock layers carrying groundwater (aquifer), both vertically and laterally. The research objective is to determine the location for drilling, if later in the study area, the groundwater potential maximally utilized. In this study, the linear symmetry electrode arrangement, the Schlumberger configuration method, is used. Data collection in the field done by using a resistivity meter. The number of geoelectric points is 12 measurement points, but in the article, four geoelectric points will be discussed that can represent all the geoelectric points that contain high aquifers. The results obtained from the geoelectric measurements carried out show a shallow groundwater layer at a depth of 5.0 - 15.0 meters with an aquifer layer in the form of sandy clay (lateral weathering). Freshwater in freshwater at a depth of 25 - 150 meters following the geoelectric point of estimation with layers of sandstone aquifer and tuffaceous clay. Shallow groundwater is fresh with small productivity can be anointed with dug wells at a depth of 5 - 15 meters potential at all geoelectric points with a discharge of 1 liter/second. Then deep groundwater is of average productivity with a well drilled at a depth of 25 – 150 meters, potentially at a specific geoelectric point with a discharge of 1 – 5 liters/second.